PEDAGANG WARUNG KELI: Studi Eko-Sosial Religius Wanita Pedagang Tradisional Di Desa Jambearum Kendal Jawa Tengah - Lutfiah, Lutfiyah (LP2M IAIN kUDUS, 2017)
Women in a family have a role as a spouse, a sweetheart or a mother. Women have a right to determine and concrete a happiness either immaterial or material. In Jambearum, Kendal, Central Java, there were some women who played a role of helping her husband, by becoming a vendor, or known as warung keli. The role woman as a wife and the role for helping husband did not make them to stop becoming a religious-social being as well. This research is a qualitative descriptive which used social anthropology approach. This research aimed to determine: 1)Women who have extra job to earn a living, are tough. 2) The time management is, these women began to accomplish domestic activities after fajr until 08.00 AM, then they started to kulaan in village market before selling around. Religius social activities were conducted as best as they can, some of them were active, others were moderate and less active. 3) The contributions given by these women can not be mentioned significantly.